Thermal shock tests to qualify different tungsten grades as plasma facing material. (12th January 2016) - Wirtz, M; Linke, J; Loewenhoff, Th; Pintsuk, G; Uytdenhouwen, I
Abstract: The electron beam device JUDITH 1 was used to establish a testing procedure for the qualification of tungsten as plasma facing material. Absorbed power densities of 0.19 and 0.38 GW m −2 for an edge localized mode-like pulse duration of 1 ms were chosen. Furthermore, base temperatures of room temperature, 400 °C and 1000 °C allow investigating the thermal shock performance in the brittle, ductile and high temperature regime. Finally, applying 100 pulses under all mentioned conditions helps qualifying the general damage behaviour while with 1000 pulses for the higher power density the influence of thermal fatigue is addressed. The investigated reference material is a tungsten product produced according to the ITER material specifications. The obtained results provide a general overview of the damage behaviour with quantified damage characteristics and thresholds. In particular, it is shown that the damage strongly depends on the microstructure and related thermo-mechanical properties.